Youth with a Future Program: a third sector educational technology - Balduino, Maria Aparecida Canale (2020)
This article focuses on the discussion that arises in the relationship between the public and the private in education and, more specifically, the implications that the educational technology of the Youth with a Future Program (PJF), presented, created and developed by the Unibanco Institute (IU), generates in the management of public schools. The technology is pre-qualified in the Educational Technologies Guide of the Ministry of Education (MEC) and is effective through partnerships with the MEC, the governments of the states of Ceará, Goiás, Mato Grosso do Sul, Pará and Piauí and the institute, within the framework of the High School Program Innovative/Youth with a Future, for the management of high schools. The research takes place in the context of the State role redefinition, as a result of a structural crisis of the capital from the perspective of neoliberal ideology, which, as a way of overcoming it, under the argument that what is in crisis is the State, and not the capital, indicates as a way out the State reform by reducing its role, more specifically in the execution of social policies, among them, the educational ones. The methodology of the research is based on a bibliographic survey in the documents of the Unibanco Institute and its printed editorial materials. Through the materials, it can be identified that the PJF employs the market logic in public high schools and induces the schools to be accountable for the results, which incorporate changes in their pedagogical proposals and, thus, compromise the school management autonomy, violating the principle of democratic management.